Acute lymphoblastic leukaemia among Spanish children and mothers' occupation: a case-control study. Issue 1 (March 1991) - Infante-Rivard, C; Mur, P; Armstrong, B; Alvarez-Dardet, C; Bolumar, F
Abstract : STUDY OBJECTIVE–The aim was to investigate the association between mothers' occupational exposure during pregnancy and the incidence of acute lymphoblastic leukaemia in children. DESIGN–The study was a case-control investigation. A face to face interview was used to assess exposures at work and relevant confounding variables. SETTING–The study was community based and was carried out in five provinces of Spain. SUBJECTS–128 cases less than 15 years of age were interviewed (91% of those eligible). Controls (one for each case) were chosen from the census lists and were matched on year of birth, sex and municipality. MEASUREMENTS AND MAIN RESULTS–Children of mothers working at home had a relative risk (RR) of 7.0 (95% CI = 1.59-30.79) of developing acute lymphoblastic leukaemia. Exposure to organic dust was associated with a RR of 5.5 (95% CI = 1.21-24.8). There was a statistically significant interaction between exposure to organic dust and working at home. The majority of women working at home were hired by local industries to sew different types of tissues (cotton, wool, synthetic fibres) on a machine. CONCLUSION–A similar association has not been reported before: if confirmed, this finding may suggest a new health concern.